Pengembangan Bahan Ajar Media Pembelajaran Berbasis Kearifan Lokal Di SDI Mauloo - Kanisius Goreti Sangi; Tanti Diyah Rahmawati; Adi Jufriansah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
The main purpose of this research is to determine the development and validity of the development of teaching materials based on local wisdom learning media at SDI Mauloo. development of local wisdom-based learning media teaching materials at SDI Mauloo. (2) To determine the validity of the development of local wisdom-based learning media teaching materials at SDI Mauloo. This research was conducted at SDI Mauloo. This research was conducted in the even semester, starting from March 1 to April 1, 2022. This type of research is Research and Development(R&D) and the data collection tool is a questionnaire. The data sources for this research are 5th grade students and mathematics teachers at SDI Mauloo. Based on the results of these calculations, obtained for V the combined = 87.5% . Furthermore, the results of these calculations are interpreted with criteria. Based on the validity criteria, the assessment of the validator, namely for V combined = 87.5%, included in the valid criteria, so that this learning media module can be used without revision and is feasible to use during the learning process. The revisions and suggestions for improving the module are taken from the suggestions and input of the validators. So, the results of this study concluded that the mathematics learning device was a valid local wisdom-based learning media module.